Skale pomiaru w międzynarodowych badaniach marketingowych - Sobczak, Elżbieta (Measurement Scales in International Marketing Research, 2006)
The objective of the hereby study is the analysis of measurement scales types with regard to opportunities of their utilization in international research, as well as ways for the assessment of their usefulness. The following issues were discussed: equivalence of measurements run in many countries, correctness of measurement techniques applied for data collection and referring to it reliability and validity of data. Alternative approaches to applying multi-item scales were presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (16); 2006; nr 1100, s. 97-109